Experimental Evaluation of Tranexamic Acid–Loaded Porous Starch as a Hemostatic Powder. (March 2018) - Xi, Chaoyun; Zhu, Liguo; Zhuang, Yuan; Wang, Shufang; Sun, Guixiang; Liu, Yaqian; Wang, Deqing
We evaluated the effectiveness of a novel hemostatic powder called Tranexamic Acid-loaded Porous Starch (TAPS) developed recently on blood clotting activity and hemostasis. The effectiveness of TAPS was evaluated by comparing hemostatic properties with those of Quick-acting Styptic Powder (QSP) and Compound Microporous Polysaccharide Haemostatic powder (CMPHP). The blood clotting activities of human blood were analyzed by thromboela-stogram (TEG) assays in vitro. The hemostatic effectiveness in vivo was evaluated using a rat model with hepatic traumatic hemorrhage. The blood loss and standardized bleeding score, which reflects the degree of bleeding after treatment with styptic powder, were used to evaluate hemostatic efficacy. In vitro, the values of TEG parameters in TAPS group were significantly different, compared with untreated controls or CMPHP group (p < 0.05). In vivo, the application of QSP, CMPHP and TAPS led to significantly decreased post-treatment blood loss than in the control group (p < 0.01). The scores of the groups treated with QSP, CMPHP and TAPS (0, 0.2±0.422, 0.3±0.483, respectively) were significant lower than with gauze control (1.6±0.516) which success hemostatic was achieved at 5 minutes (p < 0.01). Hemostasis was achieved successfully within approximately 4 minutes after the application of TAPS. TAPS could help blood to form an artificial scab on a wound and to seal injuries for hemostasis to reduce blood loss in rats with hepatic trauma and hemorrhage. It was safe to use with no impact on blood clotting function or other apparent side effects.